Komunikasi Interpersonal Senior Barista dalam Proses Pelatihan Barista Pemula di Nest Coffee & Donuts Jogja - Fajar Rahmad Wibowo; Fitrinanda An Nur (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the interpersonal communication of senior baristas in the training process of novice baristas at Nest Coffee & Donuts Jogja. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, direct observation, and documentation. The informants consist of senior baristas and novice baristas who are directly involved in the training activities. The findings indicate that open, supportive, and two-way interpersonal communication plays a crucial role in enhancing the effectiveness of the training process. Senior baristas function not only as technical instructors but also as mentors who foster trust, comfort, and learning motivation among novice baristas. Although communication barriers such as differences in experience levels and work pressure are present, adaptive and empathetic communication strategies are able to minimize these obstacles. Effective interpersonal communication has a positive impact on improving technical competence, self-confidence, and the ability of novice baristas to adapt to the work culture at Nest Coffee & Donuts Jogja.